Being Catholic as Reflexive Spirituality: The Case of Religiously Involved Filipino Students - Cornelio, Jayeel (Archīum Ateneo, 2011)
What does being Catholic mean to religiously involved Filipino students? Drawing from qualitative research with undergraduates involved in campus-based Catholic organisations, this article argues that their religious identity is best characterised in terms of a reflexive spirituality. Reflexive spirituality is defined as the subjective spiritual disposition of engaging with Catholicism to ascertain its most important elements and distinguish them from the less essential ones, leading to a more meaningful internalisation and exercise of the religion. Countering any expectations of traditional religiosity, its main themes among my informants include a personal and experiential relationship with God, an action-orientated relationality, and a religious critique of the Catholic leadership and peers. Collectively, these dimensions of personal meaning, relationality, and critique help in a more effective internalisation of Catholicism. Hence, although they may have resonances with their Evangelical peers, these students do not necessarily leave the religion. As it develops tacitly among Filipino Catholic youth who are not systematically organised, this reflexive spirituality may be seen as an undercurrent of experiential religion of humanity within institutionally conservative Philippine Catholicism today.